MENINGKATKAN KETERAMPILAN VOKASIONAL BUDIDAYA MENANAM CABAI MERAH MELALUI METODE DEMONTRASI PADA ANAK TUNAGRAHITA RINGAN DI SLB YPBB KARIMUN - Muhiri; Agustina Dewi; Edi kurniawan (JURNAL JUDIKHU, 2021)
This research is a classroom action research that adapts the model of Kemmis and McTaggart. This research was conducted in 8 meetings and divided into two cycles. The research subjects were 3 students of class VII. This study uses quantitative descriptive data analysis, then followed by a comparative technique by comparing the results of pre-action and post-test. The results of the first cycle have not been able to meet the predetermined minimum success indicators. In the first cycle, all subjects have not been able to achieve the minimum completeness criteria that have been determined, which is 70. So it is necessary to provide more intensive assistance and stabilization in the second cycle. In cycle II, TH subjects scored 89 with very good criteria, TA subjects scored 93 with very good criteria and AR subjects scored 82 with very good criteria. The increase in the value of the results of the Red Chili Cultivation skill was followed by an increase in the quality of learning during the implementation of the Red Chili Cultivation process. So it can be concluded that the cultivation of Red Chili Planting through the demonstration method can improve the vocational skills of class VII mentally retarded children at SLB YPBB Karimun.